World Bank Group Press Conference at the 2021 Spring Meetings, April 7, 2021 - Malpass, David (World Bank, Washington, DC, 2021)
David Malpass, President of the World Bank, discussed vaccines, climate, and debt. The World Bank commitments grew a record amount both in percent terms and dollar terms in 2020. The Bank is providing financing for several of the countries and they can be large-scale programs, but the countries are working to arrange delivery schedules from the various vaccine providers. That will be an important part of the recovery. The Bank completed a big vaccination operation through Board, which makes financing available to Bangladesh and also technical assistance from the World Bank, which is very helpful to the countries as they try to enter contract discussions, and also as they work within their health systems in order to vaccinate people. The Bank is working actively on biodiversity and agricultural challenges facing Brazil.